2004
DOI: 10.1093/genetics/166.2.901
|View full text |Cite
|
Sign up to set email alerts
|

A New Deletion of the Mouse Y Chromosome Long Arm Associated With the Loss of Ssty Expression, Abnormal Sperm Development and Sterility

Abstract: The mouse Y chromosome carries 10 distinct genes or gene families that have open reading frames suggestive of retained functionality; it has been assumed that many of these function in spermatogenesis. However, we have recently shown that only two Y genes, the testis determinant Sry and the translation initiation factor Eif2s3y, are essential for spermatogenesis to proceed to the round spermatid stage. Thus, any further substantive mouse Y-gene functions in spermatogenesis are likely to be during sperm differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Studies in mice have shown an important relationship between certain Y chromosome deletions and sperm head abnormalities (Suh et al, 1989;Styrna et al, 1991Styrna et al, , 2003Toure et al, 2004). Toure et al (2004) showed that Yq deletion with abolished Ssty expression resulted in severe sperm morphological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in mice have shown an important relationship between certain Y chromosome deletions and sperm head abnormalities (Suh et al, 1989;Styrna et al, 1991Styrna et al, , 2003Toure et al, 2004). Toure et al (2004) showed that Yq deletion with abolished Ssty expression resulted in severe sperm morphological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice have shown an important relationship between certain Y chromosome deletions and sperm head abnormalities (Suh et al, 1989;Styrna et al, 1991Styrna et al, , 2003Toure et al, 2004). Toure et al (2004) showed that Yq deletion with abolished Ssty expression resulted in severe sperm morphological abnormalities. Similarly, reduced Rbm expression in mice has been suggested to be responsible for, or to contribute to, the abnormal sperm development (Mahadevaiah et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sly , Ssty1 , Ssty2 as multicopy genes with highly repetitive DNA sequences, are located at the long arm of mouse Y chromosome (MSYq) (Fig. 1 A) (Toure et al, 2004 ). To target the repetitive sequence on Y chromosome via CRISPR/Cas9, firstly we designed three sgRNAs targeting each gene, with each sgRNA recognizing more than 100 copies of DNA on MSY (Fig.…”
mentioning
confidence: 99%
“…In our study, all these genes except for Usp9y, Sry, and Rbmy were transcribed at high levels in the XY oocytes of 50-60 µm. By contrast, the newly acquired ampliconic gene families on the long arm, Sly, Ssty, and Srsy, which are reported to be expressed predominantly in the male germline (Toure et al, 2004;Reynard and Turner, 2009), were undetectable in XY oocytes. However, other newly identified but poorly characterized genes on the Y long arm were transcribed at moderate levels in XY oocytes.…”
Section: Transcription Of Y-linked Genes In Xy Oocytesmentioning
confidence: 83%